Disclosure of their HIV status to HIV-infected children participating in the ARROW trial in Entebbe, Uganda - Ntege, P. Nahirya; Kyarimpa, J.; Dangarembizi, M. Bwakura; Nankya, F.; Namuddu, R.; Katuramu, R.; Bagurukira, E.; Lutaakome, J.; Aber, M.; Musinguzi, M.; Munderi, P. (WEPE, 2010)
HIV-infected children depend upon adults for their HIVrelated care. It has been suggested that knowledge of HIV status among older children may improve adherence to antiretroviral therapy (ART). The Ugandan National ART guidelines recommend children aged > 8 years be informed of their HIV status. There are few documented experiences of disclosure of HIV status to children on ART.
Keywords: HIV; ARROW; status